EXPLORING BEHAVIORAL PROBLEMS AND PSYCHOLOGICAL ADJUSTMENT OF SPECIAL CHILDREN WITH LEARNING DISABILITIES - Tariq Rasheed; Ayesha Siddiqua; Sadia Naureen (Journal of University Medical & Dental College, 2016)
ABSTRACT:OBJECTIVES: The objective of the study is to explore common behavioral problems among special children who suffer from learning disabilities and examine whether their learning disabilities can cause psychological adjustment problems in children and split up as per gender.STUDY DESIGN: Interpretive Phenomenological AnalysisPLACE & DURATION OF STUDY: Study was conducted from March, 2015toAugust, 2015 in GISL, Okara and GHSS(HIC), Chiniot.METHOD: Inclusion and Exclusion criteria were followed to gather data for this study. Slow learner children with learning disabilities (dyslexia, dysgraphia, dyscalculia) and hearing impaired children with dysgraphia (writing difﬁculties) with an age range 6-18 years and IQ ranges 70-90were included whereas slow learner children without learning disability and hearing impaired children without learning disability were excluded. Sample of 110 was selected which comprised of 50(Hearing Impaired children with learning disability), (20 girls and 30 boys) and 60 slow learners with learning disability(30 boys and 30 girls) using purposive sampling technique and data was collected from parents, teachers and children with learning disabilities using semi structured interview guide for qualitative analysis and Child Behavior Checklist and Psychological Adjustment Scale for quantitative analysis.RESULTS: Results showed that special children with LD have Mean=56.95, SD=23.889 on Behavioral Checklist and on Psychological Adjustment Scale, results showed that .9% of children with LD were well adjusted, 11.8 were adjusted, 44.5% less adjusted, 37.3% were maladjusted and 5.5% were severe maladjusted out of 110 population of special children with learning disabilities whereas, as per gender, there was statistically no signiﬁcant difference on Behavioral Checklist and Psychological Adjustment Scale.CONCLUSION: Learning Disabilities have comorbidity of behavioral problems and maladjustment, Furthermore, boys and girls with learning disabilities have same tendency of psychological adjustment problems and as well as behavioral problems.